2015
DOI: 10.5194/angeo-33-437-2015
|View full text |Cite
|
Sign up to set email alerts
|

The dayside magnetopause location during radial interplanetary magnetic field periods: Cluster observation and model comparison

Abstract: Abstract. The present work has investigated the midlatitudinal magnetopause locations under radial interplanetary field (RIMF) conditions. Among 262 (256) earthward (sunward) RIMF events from years of 2001 to 2009, Cluster satellites have crossed the magnetopause 22(12) times, with 10 (7) events occurring at midlatitudes. The observed midlatitudinal magnetopause positions are compared with two empirical magnetopause models (Shue et al., 1998;Boardsen et al., 2000) (hereafter referred to as the Shue98 model and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The previous results show that the magnetopause moves about 2 R E sunward in comparison with the model predictions, having a bullet‐like or globally expanded structure [ Slavin et al ., ; Dušík et al ., ; Jelínek et al ., ; Suvorova et al ., , Suvorova and Dmitriev , , , Park et al ., ]. The magnetopause also shows a local time asymmetry in its size and shape [ Huang et al ., ]. It was reported that empirical models underestimate the magnetopause position in the postnoon sector (12–17 magnetic local time (MLT)) and overestimate the magnetopause positions in the dawn (5–8 MLT) and dusk (18–21 MLT) sectors.…”
Section: Introductionmentioning
confidence: 99%
“…The previous results show that the magnetopause moves about 2 R E sunward in comparison with the model predictions, having a bullet‐like or globally expanded structure [ Slavin et al ., ; Dušík et al ., ; Jelínek et al ., ; Suvorova et al ., , Suvorova and Dmitriev , , , Park et al ., ]. The magnetopause also shows a local time asymmetry in its size and shape [ Huang et al ., ]. It was reported that empirical models underestimate the magnetopause position in the postnoon sector (12–17 magnetic local time (MLT)) and overestimate the magnetopause positions in the dawn (5–8 MLT) and dusk (18–21 MLT) sectors.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found that P SW under radial IMF intervals is smaller than that under nonradial IMF intervals [i.e., Merka et al ., ; Suvorova et al ., ; Pi et al ., ; Huang et al ., ]. Since the reduction of P SW also controls the expansion of the magnetopause for radial IMF, it is unclear whether the expanded magnetopause during radial IMF conditions is solely related to the IMF orientation [ Suvorova et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…As utilized in previous work (e.g. Huang T et al, 2015), the specific criterion used to select dominant IMF B x events involves the IMF cone angle, calculated as the angle between the IMF vector and the Sun−Earth direction. It is calculated as…”
Section: Data: Sources and Processing Methodsmentioning
confidence: 99%